Pengaruh Financial Stability, Financial Target, Ineffective Monitoring Dan Capability Terhadap Kecurangan Laporan Keuangan Pada Perusahaan Yang Terdaftar Dalam Indeks LQ-45 Bei Periode 2013 Sampai Dengan 2015 - Bima Mahatma Hendra; Arief Himmawan Dwi Nugroho (JRAK (Jurnal Riset Akuntansi dan Bisnis), 2022)
This study aims to empirically prove the effect of financial stability, financial targets, ineffective monitoring, and capability on fraudulent financial reporting in LQ-45 companies in Indonesia. This research uses a population of LQ-45 companies that have gone public and are listed on the IDX during the 2013-2015 period which were taken through a purposive sampling of 22 companies. The conclusion of this study is that financial stability has a significant positive effect on detecting fraudulent financial reporting; Financial target dan ineffective monitoring have no significant positive effect in detecting fraudulent financial reporting; Capability have no significant negative effect in detecting fraudulent financial reporting.